ANALISIS KINERJA INSTALASI FARMASI RSUD SUNAN KALIJAGA KABUPATEN DEMAK DENGAN PENDEKATAN BALANCED SCORECARD - , Indriyati Hadi Sulistyaningrum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
By using the Balanced Scorecard performance measurement (financial perspective, customer perspective, internal business perspective, and learning and growth perspective)